Third Soviet-American Gases and Aerosols (SAGA 3) experiment: Overview and meteorological and oceanographic conditions - Johnson, J. E.; Koropalov, V. M.; Pickering, K. E.; Thompson, Anne M.; Bond, N.; Elkins, J. W. (AGU, 1993)
The primary goal of the third joint Soviet-American Gases and Aerosols (SAGA 3) experiment was to study trace gases and aerosols in the remote marine boundary layer. SAGA 3/leg 1 took place from February 13 to March 13, 1990, aboard the former Soviet R/V Akademik Korolev and consisted of five equatorial transects (designated transects 1 through 5) between 15°N and 10°S on a cruise track from Hilo, Hawaii, to Pago-Pago, American Samoa. Specific objectives were to study (1) the oceanic distribution and air-sea exchange of biogenic trace gases; (2) photochemical cycles of C-, S-, and N-containing gases in the marine boundary layer; (3) the distribution of aerosol particles in the marine boundary layer and their physical and chemical properties; (4) interhemispheric gradients and latitudinal mixing of trace gases and aerosols; and (5) stratospheric aerosol layers. SAGA 3/leg 2 continued from March 17 to April 7, 1990, with one more equatorial transect between American Samoa and the northern coast of the Philippines (transect 6) followed by a final transect to Singapore (transect 7). During leg 2, most former Soviet measurements continued, but with the exception of measurements of nitrous oxide (N₂O) and selected halocarbons in the air and surface waters all American measurements ceased. This paper briefly summarizes the chemical measurements made by SAGA 3 investigators and presents in some detail the meteorological and hydrological characteristics encountered during SAGA 3. The meteorological analysis is based on atmospheric soundings of temperature, humidity, winds, sea surface temperature, postcruise back trajectories of winds, and satellite imagery. In general, the meteorology during SAGA 3 was typical of the location and time of year. Exceptions to this include an incipient El Niño that never developed fully, a poorly defined ITCZ on 4 of 6 equator crossings, wind speeds that were 20% greater than the decadal mean, a convective event that brought midtropospheric air to the surface (on Julian day 59), and transport of northern hemispheric air to 18°S during a synoptic scale tropical disturbance.